Metastatic neuroendocrine carcinoma in inguinal region complicated with membranous nephropathy: a case report - Xinyun Qiang; Jieyu Lu; Mujie Ye; Ruitong Xu; Qiyun Tang (Discover Oncology)
Abstract Neuroendocrine neoplasms (NENs) are rare, malignant tumors characterized by variable incidence rates globally, with an overall trend of increasing frequency. The gastrointestinal tract and lungs are the most common primary sites for NENs. Between 11% and 22% of NENs present without an identifiable primary site, with the liver being the most frequent site for metastases. However, metastasis to the inguinal lymph nodes remains uncommon. Tumor-associated kidney disease can occur in association with both solid tumors and hematologic malignancies. Membranous nephropathy is the most prevalent pathological type of tumor-associated kidney disease in patients with solid tumors, and its occurrence in patients with neuroendocrine carcinoma is extremely rare. This article discusses the case of a 72-year-old male patient with metastatic neuroendocrine carcinoma of unknown primary origin, presenting with inguinal metastasis and membranous nephropathy. It details the patient’s clinical presentation, diagnostic process, treatment plan, and prognosis, with the goal of increasing awareness and understanding of this rare condition and reviewing pertinent literature.